A?PP processing results in greater toxicity per amount of A?1-42 than individually expressed and secreted A?1-42 in Drosophila melanogaster. - Bergkvist, L.; Sandin, L.; Kågedal, K.; Brorsson, A.C. (Biology open, 2016)
The aggregation of the amyloid-? (A?) peptide into fibrillar deposits has long been considered the key neuropathological hallmark of Alzheimer's disease (AD). A? peptides are generated from proteolytic processing of the transmembrane A? precursor protein (A?PP) via sequential proteolysis through the ?-secretase activity of ?-site A?PP-cleaving enzyme (BACE1) and by the intramembranous enzyme ?-secretase. For over a decade, Drosophila melanogaster has been used as a model organism to study AD, and two different approaches have been developed to investigate the toxicity caused by AD-associated gene products in vivo In one model, the A? peptide is directly over-expressed fused to a signal peptide, allowing secretion of the peptide into the extracellular space. In the other model, human A?PP is co-expressed with human BACE1, resulting in production of the A? peptide through the processing of A?PP by BACE1 and by endogenous fly ?-secretase. Here, we performed a parallel study of flies that expressed the A?1-42 peptide alone or that co-expressed A?PP and BACE1. Toxic effects (assessed by eye phenotype, longevity and locomotor assays) and levels of the A?1-42, A?1-40 and A?1-38 peptides were examined. Our data reveal that the toxic effect per amount of detected A?1-42 peptide was higher in the flies co-expressing A?PP and BACE1 than in the A?1-42-expressing flies, and that the co-existence of A?1-42 and A?1-40 in the flies co-expressing A?PP and BACE1 could be of significant importance to the neurotoxic effect detected in these flies. Thus, the toxicity detected in these two fly models seems to have different modes of action and is highly dependent on how and where the peptide is generated rather than on the actual level of the A?1-42 peptide in the flies. This is important knowledge that needs to be taken into consideration when using Drosophila models to investigate disease mechanisms or therapeutic strategies in AD research.